Emergency Characterization of Unknown Materials - Houghton, Rick; Bennett, William (Professional trainer) (CRC Press, 2021)
Emergency Characterization of Unknown Materials, Second Edition is fully updated to serve as a portable reference that can be used in the field, and laboratory by workers who are responsible for safe response to and management of unknown hazardous materials. As with the first edition, the book emphasizes public safety and the management of life safety hazards, including strategies and emerging technologies to identify the hazards presented by an unknown material. When responding to a hazardous material emergency involving an unknown substance, firefighters and HAZMAT teams are primarily interested in protecting public safety. The book details risk analysis procedures to identify threats and vulnerabilities, analyzing them to determine how such risks can be eliminated or reduced. If an unknown material can be identified with a high degree of confidence, that can considerably change the response, and measures taken. In addition, the book covers practical field applications with updated and additional examples of field instruments. The hazard identification methods presented are intended for use by frontline workers. The test methods presented involve manipulation of small amounts of sample-using, literally, a hands-on approach. The three technologies used by first responders and military personnel to identify unknown chemicals are Raman spectroscopy, FTIR spectroscopy, and high-pressure mass spectroscopy are covered in-depth.